The Greenest Hungarian University for the Greenest Hungarian City – the University of Pécs in the light of sustainability - Daniel, Kehl; T., Kulcsár (Journal of Sustainability Perspectives, 2022)
Five years ago, the University of Pécs (UP) stated in its Green University Program mission, that every useful practice, innovation, management in the environment tend to help sustainability and sustainable administration has to be encouraged, with the aid of education and science aiming to strengthen ecological consciousness.In 2020 the University of Pécs participated for the fifth time in the international “UI GreenMetric World University Rankings”. Thanks to its conscious, disciplined environmental ambitions and related efforts, UP has been able to move forward year after year in ever-expanding rankings. 2020 UP made it to the 59th place worldwide and reaching the 1st place in Hungary, earning the Greenest Hungarian University title. The university started to build a network both on the national and international level. The University of Pécs, together with the University of Szeged, plays the role of national coordinator in the UI GreenMetric World University Rankings Network.The Green University Program is playing a more and more important role in the university life and helps to further develop the visibility of the UP brand both nationally and internationally contexts. Complex sustainability efforts provide an opportunity to address responses to challenges holistically. UP is involved in a harmonic and sustainable relationship with the environment, balancing the university and environmental interests. Besides the traditional roles of teaching and research UP is focusing on its third mission together with its stakeholders.UP as a green university is a catalyst of innovation aiming at reaching sustainable development goals. “Green thinking” is present in all aspects of life, so it is important to exploit the synergies that reinforce and shape the thinking of individuals to make “green acting” part of their everyday lives. The existence and life quality of future generations largely depend on our success in transforming our views on the world, environment, and attitude towards life. Are we ready to change our habits and save the environmental resources, to protect our environment and maintain biodiversity, to live in a sustainable way? The University of Pécs is a leader in Hungary in this mission. Due to its collaborative work together with its partners Pécs won the Greenest City of Hungary title in 2020. Keyword: sustainability, eco awareness, partnering, innovation, green university, responsibility, third mission, University of Pécs (Hungary)